THE EFFECT OF HYDROTHERAPY ON PAIN RELIEF IN KNEE OSTEOARTHRITIS PATIENTS AT DRS. H. AMRI TAMBUNAN REGIONAL HOSPITAL - Raynald Ignasius Ginting; Nurpaizah; Rabiatun Nasution (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Osteoarthritis (OA) of the knee is a common degenerative joint disease, characterized by progressive damage to the articular cartilage, changes in the subchondral bone, and synovial inflammation. This condition often causes pain, stiffness, and decreased joint function, which significantly affects the quality of life of sufferers. Hydrotherapy is an exercise program carried out in a swimming pool with various types of movements. Research Objective: To analyze the effects of Hydrotherapy on Osteoarthritis sufferers. Research Method: This is a quasi-experimental study with a one-group pre-test and post-test design. Hydrotherapy interventions were carried out twice a week for 4 weeks with a total of 8 actions, the measuring instrument used was the Visual Analog Scale (VAS). Results and Discusion: shows that pain in Osteoarthritis patients before being given Hydrotherapy was obtained an average pain of 4.82 with a standard deviation of 1.237 and the pain value in Osteoarthritis patients after being given Hydrotherapy was obtained an average pain of 2.47 with a standard deviation of 1.125 based on the data analysis value using the paired sample t-test statistical test obtained a p-value of 0.000 smaller than α 0.05. Conclusion: identifying the effect of Hydrotherapy on pain in Osteoarthritis patients.